Pengaruh Pola Asuh Orang Tua terhadap Penerimaan Bahasa Reseptif Anak Tunarungu - Imaratul Ulwiyah; Arifah Nurhadiyati (Departement of Mathematics Education, 2024)
This case study is being conducted after long observation to a child named AB. He is eight (8) years old and he doesn’t being a part of any schools. He has a problem related to the hearing. Doctor has diagnosed him as a deaf person. In his everyday life, he doesn’t do any activities in normal way such as take everything without permission, he is not able communicate with each other, and he can’t express his willing. After doing depth interview to his mother, unfortunately, his mother doesn’t apply the right parenting for him. That is why it becomes a reason that he does such things. All of these are caused by the failure of his receptive language. Normal children will process the information he got and then express it in oral language. AB doesn’t have this ability because there is a problem with his hearing. In other words, his receptive language is not running well. Referring to this condition, every parent should give best and more attention to every child with special need like AB. Some scientists say that a child like AB has the same chance to get good parenting like others. Many stimulus and exercises must given to him in order he can do many thing by himself and he can be accepted by his environment.